Returns to Education between the Self-employed and Employed Sectors: Evidence from Malaysia (The Pakistan Development Review, 2000)
Investment in human capital in terms of returns to education is considered a crucial factor that contributes to the remarkable economic growth especially in the rapidly developing countries. Since poverty and education are closely related, this paper attempts to examine whether returns to education differ between the self-employed and employed sectors in the rural Malay area in Rantau, Malaysia. Using the adjusted Mincerian Earnings function and the dummy variables approach, the empirical finding shows that returns to education do not differ between the self-employed and employed sectors in the rural Malay society. Thus, it can be deduced that there is no significant difference between the self-employed and employed sectors in those two sectors. Interestingly, it also reveals that private rates of return (ROR) increase by the level of schooling and they are the highest at the Secondary level. Finally, appropriate strategies are further suggested to alleviate poverty in the case study area.